2014
DOI: 10.1371/journal.pone.0090281
|View full text |Cite
|
Sign up to set email alerts
|

Context Specificity of Post-Error and Post-Conflict Cognitive Control Adjustments

Abstract: There has been accumulating evidence that cognitive control can be adaptively regulated by monitoring for processing conflict as an index of online control demands. However, it is not yet known whether top-down control mechanisms respond to processing conflict in a manner specific to the operative task context or confer a more generalized benefit. While previous studies have examined the taskset-specificity of conflict adaptation effects, yielding inconsistent results, control-related performance adjustments f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 59 publications
4
38
1
2
Order By: Relevance
“…For example, while several studies using the flanker task have found increases in accuracy following errors compared to correct trials (Grutzmann, Endrass, Klawohn, & Kathmann, ; Marco‐Pallares, Camara, Munte, & Rodriguez‐Fornells, ; Pontifex et al, ; Seifert, von Cramon, Imperati, Tittgemeyer, & Ullsperger, ; Strozyk & Jentzsch, ), other studies using the same paradigm have shown either the opposite pattern (Arnstein, Lakey, Compton, & Kleinow, ; Fiehler, Ullsperger, & von Cramon, ; Franken, van Strien, Franzek, & van de Wetering, ) or no difference between the conditions (Moran, Bernat, Aviyente, Schroder, & Moser, ; van den Brink et al, ). The same picture is true for other tasks, with some studies showing post‐error increases in accuracy (Danielmeier et al, ; Dutilh et al, ; Forster & Cho, ; Klein et al, ), some showing decreases (Bombeke, Schouppe, Duthoo, & Notebaert, ; Carp & Compton, ; Houtman & Notebaert, ; Jentzsch & Dudschig, ; Jonker, Seli, Cheyne, & Smilek, ; Notebaert et al, ; Notebaert & Verguts, ; Van der Borght, Braem, Stevens, & Notebaert, ), and some showing no change (e.g., Hajcak et al, ).…”
Section: Section Ii: Behavioral Studies Of Post‐error Accuracy Are Inmentioning
confidence: 83%
“…For example, while several studies using the flanker task have found increases in accuracy following errors compared to correct trials (Grutzmann, Endrass, Klawohn, & Kathmann, ; Marco‐Pallares, Camara, Munte, & Rodriguez‐Fornells, ; Pontifex et al, ; Seifert, von Cramon, Imperati, Tittgemeyer, & Ullsperger, ; Strozyk & Jentzsch, ), other studies using the same paradigm have shown either the opposite pattern (Arnstein, Lakey, Compton, & Kleinow, ; Fiehler, Ullsperger, & von Cramon, ; Franken, van Strien, Franzek, & van de Wetering, ) or no difference between the conditions (Moran, Bernat, Aviyente, Schroder, & Moser, ; van den Brink et al, ). The same picture is true for other tasks, with some studies showing post‐error increases in accuracy (Danielmeier et al, ; Dutilh et al, ; Forster & Cho, ; Klein et al, ), some showing decreases (Bombeke, Schouppe, Duthoo, & Notebaert, ; Carp & Compton, ; Houtman & Notebaert, ; Jentzsch & Dudschig, ; Jonker, Seli, Cheyne, & Smilek, ; Notebaert et al, ; Notebaert & Verguts, ; Van der Borght, Braem, Stevens, & Notebaert, ), and some showing no change (e.g., Hajcak et al, ).…”
Section: Section Ii: Behavioral Studies Of Post‐error Accuracy Are Inmentioning
confidence: 83%
“…5). This pattern not only shows that adaptive and nonadaptive posterror adjustments coexist and can be elicited by the same error, it also indicates that adaptive posterror adjustments under multitasking are subtask-specific (see also Forster & Cho, 2014). This implies that the underlying error-monitoring system is able to validly assign an error signal (e.g., postresponse conflict) to the task that caused the error.…”
Section: Error Monitoring and Posterror Adjustments In Multitaskingmentioning
confidence: 85%
“…Though related, post-error and post-conflict control adjustments are not identical phenomena (see Forster & Cho, 2014). Recent research shows that alcohol strongly affects post-error adjustments but has little impact on sequences of correct-response trials in conflict tasks (Bailey et al, 2014).…”
mentioning
confidence: 99%